(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
This study was carried out to identify and observe prevalence and pathological lesions of avian colibacillosis in commercial broiler in variation of litter type, age, farm size, source of water and season of year in Chittagong region. Colibacillosis in commercial broiler farms causes huge economic loss through a relatively high mortality and loss of production. In the present study, a total of 275 broilers of 104 farms were examined through post-mortem and among them 150 (54.55%) broiler was diagnosed as affected with any lesion of colibacillosis. The most frequent gross lesions of colibacillosis were air sacculitis (20.67%), omphalitis (12.00%), pericarditis (13.33%), perihepatitis (13.33%), peritonitis (1.33%), colisepticemia (8.00%), enteritis (8.00%) and a large number 35 (23.33%) of broiler combination of different form of colibacillosis. The microscopic lesions of these conditions were chronic passive congestion, fibrosis of liver capsule, telangiectasis, thick fibrous layer in the pericardium of heart, blunting and sloughing off villus and infiltration of lamina propria of intestine. The results obtained during the study period revealed that winter season of the year was significant (p>0.05) high risk factors of colibacillosis in broiler but litter, age, farm size, source of water were not significantly risk factor. Considering the factor it could be concluded based on pathology that colibacillosis causes high mortality and winter season was the main risk factor in broiler at Chittagong District. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 173-180